First record of Dendrobaena pygmaea (Oligochaeta: Lumbricidae) from Asia (Yokohama, Japan) - Blakemore, R. J. (Zootaxa, 2004)
The ’cosmopolitan’ lumbricid earthworm Dendrobaena pygmaea (Savigny, 1826) is reported for the first time from Asia, from the campus of Yokohama National University, Japan. It is a small detritivorous ’litter species’ or ’humus feeder’ found to have a simple intestinal typhlosole. Here it is briefly re-described, and its taxonomy and previously known distribution (in Europe, North Africa, North and South America) are discussed. A figure is provided. As Yokohama port was opened for foreign trade shortly after Commodore Perry’s visit in 1853, the incursion of this species is probably only within the last 150 years. It is not considered to pose any particular environmental risk.